Estimates of scale and scope economies in the New Zealand life insurance industry - Khaled, M; Adams, M.D; Pickford, M (School of Management Working Papers, 1995)
Recent multi-product statistical studies of life insurance industries in North America and the United Kingdom have produced mixed findings with regard to economies of scale and scope. This study presents results for the insurance industry in a small economy where the industry is comparatively unregulated. 135 pooled observations for the population of non-bank insurance companies in New Zealand for the period 1988-1992 are used in a two input/three output translog model. We find that while small companies enjoy economies of scale, the optimum plant size is modest, and medium-and large-sized companies experience a significant scale disadvantage. In contrast, all sizes of company benefit from scope economies, but such economies tend to be much greater for the larger companies.